MAKNA SIMBOLIK TARI SESANDURAN DI KABUPATEN TUBAN - Yuniar, Ni Ratih Putri; Slamet, Slamet (Greget: Jurnal Kreativitas dan Studi Tari, 2023)
This research aims to reveal the symbolic meaning that exists in the Sanduran Dance. Sesanduran dance is a dance form inspired by Sandur art in Tuban Regency. Using vocal music and accompanied by roof gongs and drums. This study describes and analyzes about: (1) the form of Sesanduran Dance which includes: movement, dancers, costumes, expressions or feelings, place of performance, (2) describes the symbolic meaning of Sesanduran Dance from the view of inner and outer aspects. To answer the form of Sesanduran Dance using theory by Slamet Md. Describing the symbolic meaning of Sesanduran Dance using theory from Allegra Fuller Synder. This research is a descriptive qualitative research. Data collection through documentation of works, literature studies, interviews and observations of Sandur and Sandur Dance. The results of this study show that the form of dance cannot be separated from the dance former consisting of movement, dancers, costumes, expressions or feelings, the place of performance. The symbolic meaning of Sesanduran Dance is seen from the outside aspect looking at the expression side of society. The compiler of Sesanduran Dance was inspired by the bancik scene in Sandur art in Tuban Regency. This section gives the understanding that humans in their lives are full of journeys that must be passed according to the cycle of life. There are nine motion motives that undergo levels of stimulation, transformation, and unity. Seven sets of motion are the foothold of bancik scenes and two motion motifs are typical movements of Sandur art in Tuban Regency.